Ammonia removal in aquaculture system by membrane based separation system - Rosalam Sarbatly; Duduku Krishnaiah; Yeo Kiam Beng @ Abdul Noor; Saleem Mustafa; Rakmi Abd Rahman (Universiti Malaysia Sabah, 2008)
No abstract